Amniotic Fluid Phthalate Levels and Male Fetal Gonad Function. Issue 1 (January 2015) - Jensen, Morten Søndergaard; Anand-Ivell, Ravinder; Nørgaard-Pedersen, Bent; Jönsson, Bo A. G.; Bonde, Jens Peter; Hougaard, David M.; Cohen, Arieh; Lindh, Christian H.; Ivell, Richard; Toft, Gunnar
Abstract : Background: Prenatal exposure to phthalates may pose a threat to human male reproduction. However, additional knowledge about the in vivo effect in humans is needed, and reported associations with genital abnormalities are inconclusive. We aimed to study prenatal di(2-ethylhexyl) phthalate (DEHP) and diisononyl phthalate (DiNP) exposure in relation to cryptorchidism, hypospadias, and human fetal Leydig cell function. Methods: We studied 270 cryptorchidism cases, 75 hypospadias cases, and 300 controls. Second-trimester amniotic fluid samples were available from a Danish pregnancy-screening biobank (n = 25, 105) covering 1980–1996. We assayed metabolites of DEHP and DiNP (n = 645) and steroid hormones (n = 545) by mass spectrometry. We assayed insulin-like factor 3 by immunoassay (n = 475) and analyzed data using linear or logistic regression. Results: Mono(2-ethyl-5-carboxypentyl) phthalate (5cx-MEPP, DEHP metabolite) was not consistently associated with cryptorchidism or hypospadias. However, we observed an 18% higher (95% confidence interval [CI] = 5%–33%) testosterone level, and a 41% lower (−56% to −21%) insulin-like factor 3 level in the highest 5cx-MEPP tertile compared with the lowest. Mono(4-methyl-7-carboxyheptyl) phthalate (7cx-MMeHP, DiNP metabolite) showed elevated odds ratio point estimates for having cryptorchidism (odds ratio = 1.28 [95% CI = 0.80 to 2.01]) and hypospadias (1.69 [0.78 to 3.67]), but was not consistently associated with the steroid hormones or insulin-like factor 3. Conclusions: Data on the DEHP metabolite indicate possible interference with human male fetal gonadal function. Considering the DiNP metabolite, we cannot exclude (nor statistically confirm) an association with hypospadias and, less strongly, with cryptorchidism. Abstract : Supplemental Digital Content is available in the text.